Atividades profissionais da enfermagem no contexto hospitalar: influências nas relações de trabalho - Medeiros, Angelica Teresa Nascimento de (2010)
The present study is based on an analysis of professional work relationships in the nursing team from the task/skills of its members as a contribution to understanding the work process in nursing. It is aimed to identify the skills of the nursing team members through the vision of nurses, technicians and nursing assistants, thus it attempts to find strategies to improve the health assistance to patients. It is a descriptive and analytical study with a qualitative approach grounded in theoretical and methodological framework of Symbolic Interactionism. The research was carried out in the participant work place, a Public Hospital of Reference for the SUS, located in the eastern health district of Natal/RN. Nineteen nursing professionals participated in the study, which seven was nurse and twelve nursing technician. As procedure to collect data we used an unstructured interview accompanied by a standard topic guide which was recorded and later transcribed. The content analysis was chosen as the main methodology to analyze the discussion, which gave rise to thematic categories that were considered relevant based on the theoretical framework of this study, and the interactionist theory. This study was in accordance with the ethical principles of the Resolution nº. 196/96, it has obtained an appropriate consent of the UFRN Research Ethics Committee. The results indicate that the professionals seen the nursing as a profession strongly attached to the health care process and as a profession that acquired a scientific status very recently. Regarding to the nursing functions in the work process in nursing, the professionals they identified the manage/administer category as the main activities developed by these professionals, thus the education and complex care in nursing categories. Concerning to the technicians and nursing assistants functions, it was figured out in the professional s opinion that there is not distinction among the attribution of these categories. The interviewed were unanimous in report that these professionals are more involved in direct patient health care through performance of basic duties in nursing care. Finally, with regard to the work relationship among nursing team members, the majority of those interviewed see this relationship as disharmony and quarrelsome and in general, there is not bond between categories that comprise the process of work in nursing. On the basis of our results we consider the importance of knowing the meaning of nursing given by these professionals; also their skills could be useful as basis to identify problems, which source could be detected in the power relationship, deviations of functions, gap between design (knowledge) and performance (doing) work, besides the loss of the global activities view in the process of nursing work